2013
DOI: 10.1126/science.1233521
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Gut Microbiome Drive Hormone-Dependent Regulation of Autoimmunity

Abstract: Microbial exposures and sex hormones exert potent effects on autoimmune diseases, many of which are more prevalent in women. We demonstrate that early-life microbial exposures determine sex hormone levels and modify progression to autoimmunity in the nonobese diabetic (NOD) mouse model of type 1 diabetes (T1D). Colonization by commensal microbes elevated serum testosterone and protected NOD males from T1D. Transfer of gut microbiota from adult males to immature females altered the recipient's microbiota, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
1,478
9
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,673 publications
(1,567 citation statements)
references
References 56 publications
66
1,478
9
14
Order By: Relevance
“…Multiple peaking phenomenons in the PK profiles suggest a potential role of microbiome in deconjugation of glucuronides, indicating another potential reasons of interindividual variability. This is consistent with the Markle et al 47. data, which revealed that transfer of cecal contents from male mice to female mice was associated with increased circulating testosterone in female mice.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple peaking phenomenons in the PK profiles suggest a potential role of microbiome in deconjugation of glucuronides, indicating another potential reasons of interindividual variability. This is consistent with the Markle et al 47. data, which revealed that transfer of cecal contents from male mice to female mice was associated with increased circulating testosterone in female mice.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, microbial transplantation of male cecum gut flora to females increases serum testosterone levels in both sham and ovariectomized females. 45 Based on these accumulated findings, we hypothesize that the hypertension seen in PCOS has early origins in dysbiosis caused by in utero exposure to androgen excess. As a first step to testing this hypothesis, we examined whether in utero exposure to maternal hyperandrogenemia can persistently alter the microbiome of female rat offspring and lead to hypertension in adulthood.…”
Section: Introductionmentioning
confidence: 93%
“…Differences in gut microbial composition between two sexes play a major role in this sex bias and contribute to the differential testosterone levels in male and female NOD mice [60,61]. Accordingly, germ free NOD mice lose the sex bias for diabetes incidence and both sexes show a similar rate of disease incidence [61].…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…This points to the critical role of male hormones in shaping gut microflora. Transfer of gut microbiota from adult male to young female NOD mice induces elevation of testosterone levels that is beneficial in reducing diabetes incidence [60]. Blocking of androgen receptors in recipient mice abolishes this protective effect [60] that points to the prime role of male hormone signaling in disease prevention.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation